Method for continuously manufacturing high-strength and high-toughness protein-like fibers
Through the continuous manufacturing method, the spinneret and multi-stage roller collector technology, differential stretching and heat treatment of protein-like solutions are solved, and the problem of difficult existing fiber materials to have high strength and high toughness is prepared with excellent performance.
Patent Information
- Application Number
- CN202411893678.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
Existing fiber materials are difficult to have both high strength and high toughness, and the preparation conditions for recombinant spider silk protein fibers obtained through genetic engineering are complex, and their performance is not as good as that of natural spider silk fibers.
By using a continuous manufacturing method, the protein-like solution is formed in the solidification bath through the spinneret, and the multi-stage roller collector is used for differential stretching and heating treatment to form high-strength and high-tough protein-like fibers.
High-strength and high-toughness protein-like fiber preparation, with fiber strength up to 300-400MPa, ductility up to 900-1000%, and performance is better than natural silk and other synthetic protein fibers.
Smart Images

Figure CN119640417A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fiber manufacturing, and in particular to a method for continuously manufacturing high-strength and high-tenacity protein fibers. Background Art
[0002] Fibers have a wide range of applications in all aspects of human life, from clothes and ropes in daily life to parachute ropes, space suits, bulletproof fabrics in the high-tech field. However, it is difficult for current fiber materials to have both high strength and high toughness. For example, fibers such as Kevlar and carbon fiber have excellent tensile strength, but poor fiber ductility and toughness; fibers such as spandex and rubber yarn have excellent ductility, elasticity and toughness, but are often weak in strength. Therefore, it is urgent to develop high-strength and high-toughness fibers to meet the development needs of society.
[0003] Spider silk is one of the most excellent fiber materials in nature. It has the characteristics of high strength and high toughness, and its mechanical properties exceed those of steel wire and Kevlar fiber. The excellent mechanical properties of spider silk are closely related to the microstructure inside the spider silk. At the microscopic level, spider silk contains β-sheet crystallites, α helices and amorphous segments. β-sheet crystallites as crosslinking points give spider silk excellent strength characteristics, α helices and amorphous segments give spider silk excellent ductility, and rich secondary structures give spider silk excellent strength and toughness. However, spiders have the characteristics of cannibalism, which makes them unable to be bred on a large scale, and spider silk production efficiency is low, which is far from meeting the demand for material use. Therefore, it is very challenging to obtain high-strength and high-toughness spider silk fibers through artificial breeding methods. Although genetic engineering technology has been used to express spider silk protein genes using microorganisms to obtain recombinant spider silk proteins for decades, it still faces the difficulties of complex spider silk preparation conditions that are difficult to imitate in vitro, unstable fiber preparation conditions, and poor performance of recombinant spider silk fibers compared to natural spider silk fibers. Summary of the invention
[0004] The purpose of the present invention is to provide a method for continuously manufacturing high-strength and high-tenacity protein fibers, thereby solving the problem in the prior art that current fiber materials are difficult to have both high strength and high tenacity characteristics.
[0005] In order to solve the above problems, the present invention adopts the following technical solutions:
[0006] According to a first aspect of the present invention, there is provided a method for continuously manufacturing high-strength and high-tenacity protein-like fibers, comprising the following steps: S1, pumping a protein-like solution with a mass concentration of 15-25% to a spinneret through a catheter, and immersing the spinneret in a coagulation bath solution to form protein-like fibrils in the coagulation bath; S2, using a multi-stage roller collector to continuously collect the protein-like fibrils by differential stretching, and the differential stretching multiple is 2-10 times; S3, placing the collected protein-like fibrils into an oven, and heating them at 90°C-190°C for 10min-120min to obtain a high-strength and high-tenacity protein-like fiber.
[0007] Preferably, in step S1, the solvent of the protein-like solution is dimethylformamide (DMF), dimethylacetamide (DMA) or dimethyl sulfoxide (DMSO) or a mixture thereof in any ratio, and the mass concentration of the protein-like solution is 15-20%. Most preferably, the mass concentration of the protein-like solution is 15%.
[0008] Preferably, in step S1, the coagulation bath solution is water, methanol, ethanol or isopropanol, and isopropanol is most preferred.
[0009] Preferably, in step S2, the extrusion speed of the protein solution from a single spinneret is 3 μL / min-50 μL / min, and most preferably 10 μL / min.
[0010] Preferably, in step S2, the differential stretching ratio is 8-10 times, and most preferably 10 times.
[0011] Preferably, in step S3, the heating temperature is 100°C-190°C, and the heating time is 60 min-120 min. Most preferably, the heating treatment is performed at 100°C for 60 min.
[0012] Preferably, Desmopan (a thermoplastic polyurethane, TPU) material produced by Bayer is used as raw material, thereby obtaining a high-strength and high-toughness protein-like fiber, which is of great significance to national development.
[0013] According to a preferred embodiment of the present invention, a method for continuously manufacturing high-strength and high-tenacity protein-like fibers is provided, comprising the following steps: a protein-like solution with a mass concentration of 15% is pumped to a spinneret through a catheter, the spinneret is immersed in an isopropanol coagulation bath solution, and protein-like fibrils are formed in the coagulation bath, and the extrusion speed of the protein-like solution from a single spinneret is 10 μL / min; the protein-like fibrils are collected by continuous differential stretching using a multi-stage roller collector, and the differential stretching multiple is 10 times; the collected protein-like fibrils are placed in an oven, and heated at 100°C for 60 minutes to obtain a high-strength and high-tenacity protein-like fiber.
[0014] According to another preferred embodiment of the present invention, there is provided a method for continuously manufacturing high-strength and high-tenacity protein-like fibers, comprising the following steps: pumping a protein-like solution with a mass concentration of 15% to a spinneret through a catheter, immersing the spinneret in an ethanol coagulation bath solution, forming protein-like fibrils in the coagulation bath, and the extrusion speed of the protein-like solution from a single spinneret is 10 μL / min; using a multi-stage roller collector to continuously differentially stretch and collect the protein-like fibrils, and the differential stretching multiple is 10 times; placing the collected protein-like fibrils into an oven, and heating them at 120°C for 60 minutes to obtain a high-strength and high-tenacity protein-like fiber.
[0015] According to a second aspect of the present invention, there is provided a high-strength and high-tenacity protein fiber continuously manufactured by the above method.
[0016] Inspired by spider silk, the inventors used wet spinning technology to develop a continuous bionic manufacturing method for high-strength and high-toughness bionic protein-like fibers. By guiding the formation of microcrystals within the fibers, protein-like fibers with excellent mechanical properties were obtained. The performance is better than natural silk and can even be comparable to natural spider silk.
[0017] The inventive point of the present invention mainly lies in that a high-strength and high-toughness protein-like fiber is prepared by optimizing the reaction reagents and experimental parameters, especially by inducing the formation of a microcrystalline structure in the protein-like fiber through optimized coagulation bath components, differential stretching process and heating treatment process, thereby enhancing the mechanical properties of the bionic fiber. This method can greatly improve the mechanical properties of the material, thereby reducing the amount of material used under the same performance environment, reducing the preparation cost of the molding material, and improving the quality of the molding material.
[0018] Compared with the prior art, the present invention provides a method for continuously manufacturing high-strength and high-tenacity protein-like fibers, including pumping a protein-like solution to a spinneret through a catheter, immersing the spinneret in a coagulation bath solution, forming protein-like fibrils in the coagulation bath, collecting the protein-like fibrils through a roller collector, and continuously differentially stretching and heating the protein-like fibrils through a multi-stage roller collector to obtain protein-like fibers. The present invention provides a method for biomimetic preparation of protein-like fibers with excellent mechanical properties by using protein-like spinning raw materials, utilizing wet spinning technology, and adjusting spinning parameters, especially further improving the strength and toughness of protein-like materials, with fiber strength as high as 300-400Mpa, and ductility as high as 900-1000%. The mechanical properties of the protein-like fibers prepared by the method of the present invention are significantly better than those of natural fibers represented by silk and currently known synthetic protein fibers, expanding the application prospects of protein-like fibers and opening up the application of protein-like fibers in high-tech fields such as biomedicine; the method for preparing high-strength and high-tenacity protein-like fibers of the present invention is simple in process and low in cost, does not involve large-scale changes to existing equipment, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a fiber tensile test curve diagram of Inventive Example 1;
[0020] Figure 2 This is a fiber tensile test curve diagram of Inventive Example 2;
[0021] Figure 3 This is a fiber tensile test curve diagram of Inventive Example 3;
[0022] Figure 4 This is a fiber tensile test curve diagram of Inventive Example 4;
[0023] Figure 5 This is a fiber tensile test curve diagram of Inventive Example 5;
[0024] Figure 6 This is a fiber tensile test curve diagram of Inventive Example 6;
[0025] Figure 7 is a fiber tensile test curve diagram of Inventive Example 7;
[0026] Figure 8 is a fiber tensile test curve diagram of Inventive Example 8;
[0027] Fig. 9 is a fiber tensile test curve diagram of Inventive Example 9;
[0028] Fig.10 is a fiber tensile test curve diagram of Inventive Example 10;
[0029] Fig.11 is a fiber tensile test curve diagram of Inventive Example 11;
[0030] Fig.12 is a fiber tensile test curve diagram of Inventive Example 12;
[0031] Fig.13 is a fiber tensile test curve diagram of Inventive Example 13;
[0032] Fig.14 This is a fiber tensile test curve diagram of Inventive Example 14. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with specific examples. It should be understood that the following examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional operations in the art, or according to the experimental methods recommended by the instrument and equipment manufacturers. The reagents and materials used in the examples can be obtained from commercial sources unless otherwise specified.
[0034] The invention provides a method for continuously manufacturing high-strength and high-tenacity protein-like fibers, which includes the preparation of a protein-like solution, the preparation of a coagulation bath, the setting of a roller collector and a heating temperature, and the like.
[0035] Example 1
[0036] Weigh 1.5 g of protein-like raw material solid into a glass bottle, add DMSO to a total mass of 10 g, seal and shake at room temperature to dissolve, and obtain a protein-like solution with a mass concentration of 15%. The protein-like solution is centrifuged to remove bubbles and set aside.
[0037] Take 50 mL of methanol and place it in a small plastic cup as a coagulation bath.
[0038] Use a syringe to draw 1 mL of protein-like solution, set the extrusion speed of the protein-like solution of a single spinneret, that is, the pumping speed is 10 μL / min, after the protein-like solution is found to be extruded from the spinneret, place the spinneret in a coagulation bath, and the protein-like fiber is formed and precipitated into a fiber shape in the coagulation bath. After stabilization, take out the fiber head and collect it on a roller collector. The roller collector speed is 1 m / min.
[0039] The test results of fiber mechanical properties are as follows Figure 1 As shown, the results show that the protein-like fiber strength is about 60MPa, the ductility is 750%, and the fiber mechanical curve shows that the fibers are uneven and there is a performance gap between different fibers.
[0040] Example 2
[0041] Weigh 1.5 g of protein-like raw material solid into a glass bottle, add DMSO to a total mass of 10 g, seal and shake at room temperature to dissolve, and obtain a protein-like solution with a mass concentration of 15%. The protein-like solution is centrifuged to remove bubbles and set aside.
[0042] Take 50 mL of ethanol and place it in a small plastic cup as a coagulation bath.
[0043] Use a syringe to draw 1 mL of protein-like solution and set the pumping speed to 10 μL / min. After the protein-like solution is found to be extruded from the spinneret, the spinneret is placed in a coagulation bath. The protein-like fibers are formed and precipitated into fibers in the coagulation bath. After stabilization, the fiber heads are taken out and collected on a roller collector at a speed of 1 m / min.
[0044] The test results of fiber mechanical properties are as follows Figure 2 As shown, the results show that the protein-like fiber strength is about 80MPa, the ductility is about 1000%, and the fiber mechanical curve shows that the fiber performance is relatively uniform. Compared with Example 1, this example uses an ethanol coagulation bath instead of a methanol coagulation bath, which proves that the ethanol coagulation bath is better than the methanol coagulation bath and is more conducive to improving the fiber mechanical properties.
[0045] Example 3
[0046] Weigh 1.5 g of protein-like raw material solid into a glass bottle, add DMSO to a total mass of 10 g, seal and shake at room temperature to dissolve, and obtain a protein-like solution with a mass concentration of 15%. The protein-like solution is centrifuged to remove bubbles and set aside.
[0047] Take 50 mL of isopropanol and place it in a small plastic cup as a coagulation bath.
[0048] Use a syringe to draw 1 mL of protein-like solution and set the pumping speed to 10 μL / min. After the protein-like solution is found to be extruded from the spinneret, the spinneret is placed in a coagulation bath. The protein-like fibers are formed and precipitated into fibers in the coagulation bath. After stabilization, the fiber heads are taken out and collected on a roller collector at a speed of 1 m / min.
[0049] The test results of fiber mechanical properties are as follows Figure 3 As shown, the results show that the protein-like fiber strength is about 120MPa, the ductility is about 1000%, and the fiber mechanical curve shows that the fiber performance is uniform. Compared with Example 1 and Example 2, this example uses an isopropanol coagulation bath, which proves that the isopropanol coagulation bath is better than the methanol and ethanol coagulation baths, and this condition is more conducive to improving the mechanical properties of the fiber.
[0050] Example 4
[0051] Weigh 1.5 g of protein-like raw material solid into a glass bottle, add DMSO to a total mass of 10 g, seal and shake at room temperature to dissolve, and obtain a protein-like solution with a mass concentration of 15%. The protein-like solution is centrifuged to remove bubbles and set aside.
[0052] Take 50 mL of ultrapure water and place it in a small plastic cup as a coagulation bath.
[0053] Use a syringe to draw 1 mL of protein-like solution and set the pumping speed to 10 μL / min. After the protein-like solution is found to be extruded from the spinneret, the spinneret is placed in a coagulation bath. The protein-like fibers are formed and precipitated into fibers in the coagulation bath. After stabilization, the fiber heads are taken out and collected on a roller collector at a speed of 1 m / min.
[0054] The test results of fiber mechanical properties are as follows Figure 4 As shown, the results show that the protein-like fiber strength is about 50MPa, the ductility is about 500%, and the fiber mechanical curve shows that the fiber performance uniformity is poor. Compared with Example 1, the present invention uses an ultrapure water coagulation bath, which proves that this condition is not conducive to improving the fiber mechanical properties.
[0055] Example 5
[0056] Weigh 1.0 g of protein-like raw material solid into a glass bottle, add DMSO to a total mass of 10 g, seal and shake at room temperature to dissolve, and obtain a protein-like solution with a mass concentration of 10%. The protein-like solution is centrifuged to remove bubbles and set aside.
[0057] Take 50 mL of methanol and place it in a small plastic cup as a coagulation bath.
[0058] Use a syringe to draw 1 mL of protein-like solution and set the pumping speed to 10 μL / min. After the protein-like solution is found to be extruded from the spinneret, the spinneret is placed in a coagulation bath. The protein-like fibers are formed and precipitated into fibers in the coagulation bath. After stabilization, the fiber heads are taken out and collected on a roller collector at a speed of 1 m / min.
[0059] The test results of fiber mechanical properties are as follows Figure 5 As shown, the results show that the protein-like fiber strength is about 15MPa, the ductility is about 500%, and the fiber mechanical curve shows that the fiber performance is poor. Compared with Example 1, this example uses a lower protein-like raw material concentration (10%, lower than 15% mass concentration), which proves that this condition is not conducive to improving the fiber mechanical properties.
[0060] Example 6
[0061] Weigh 2.0 g of protein-like raw material solid into a glass bottle, add DMSO to a total mass of 10 g, seal and shake at room temperature to dissolve, and obtain a 20% mass concentration protein-like solution. Centrifuge the protein-like solution to remove bubbles and set aside.
[0062] Take 50 mL of methanol and place it in a small plastic cup as a coagulation bath.
[0063] Use a syringe to draw 1 mL of protein-like solution and set the pumping speed to 10 μL / min. After the protein-like solution is found to be extruded from the spinneret, the spinneret is placed in a coagulation bath. The protein-like fibers are formed and precipitated into fibers in the coagulation bath. After stabilization, the fiber heads are taken out and collected on a roller collector at a speed of 1 m / min.
[0064] The test results of fiber mechanical properties are as follows Figure 6 As shown, the results show that the protein-like fiber strength is about 55MPa, the ductility is about 900%, and the fiber mechanical curve shows that the fiber performance is relatively uniform. Compared with Example 1, this example uses a higher protein-like raw material concentration (20%, higher than 15% mass concentration), which is not conducive to improving the fiber mechanical properties.
[0065] Example 7
[0066] Weigh 2.5 g of protein-like raw material solid into a glass bottle, add DMSO to a total mass of 10 g, seal and shake at room temperature to dissolve, and obtain a protein-like solution with a mass concentration of 25%. The protein-like solution is centrifuged to remove bubbles and set aside.
[0067] Take 50 mL of methanol and place it in a small plastic cup as a coagulation bath.
[0068] Use a syringe to draw 1 mL of protein-like solution and set the pumping speed to 10 μL / min. After the protein-like solution is found to be extruded from the spinneret, the spinneret is placed in a coagulation bath. The protein-like fibers are formed and precipitated into fibers in the coagulation bath. After stabilization, the fiber heads are taken out and collected on a roller collector at a speed of 1 m / min.
[0069] The test results of fiber mechanical properties are as follows Figure 7 As shown, the results show that the protein-like fiber strength is about 40MPa, the ductility is about 900%, and the fiber mechanical curve shows that the fiber performance uniformity is deteriorated. Compared with Example 1, this example uses a higher protein-like raw material concentration (25%, higher than 15% mass concentration), which is not conducive to improving the fiber mechanical properties. Examples 5, 6, and 7 prove that the optimal mass concentration of the protein-like raw material is 15%.
[0070] Example 8
[0071] Weigh 1.5 g of protein-like raw material solid into a glass bottle, add DMSO to a total mass of 10 g, seal and shake at room temperature to dissolve, and obtain a protein-like solution with a mass concentration of 15%. The protein-like solution is centrifuged to remove bubbles and set aside.
[0072] Take 50 mL of methanol and place it in a small plastic cup as a coagulation bath.
[0073] 1 mL of protein-like solution was drawn with a syringe, and the pumping speed was set to 10 μL / min. After the protein-like solution was extruded from the spinneret, the spinneret was placed in a coagulation bath, and the protein-like fibers were formed and precipitated into fibers in the coagulation bath. After stabilization, the fiber heads were taken out and collected on a roller collector at a speed of 1 m / min. The roller collector was set with a rear roller collector at a speed of 2 m / min, and differential stretching was performed to obtain 2-fold stretched protein-like fibers.
[0074] The protein-like fibers were placed in an oven at 120°C for heat treatment for 1 hour.
[0075] The test results of fiber mechanical properties are as follows Figure 8 As shown, the fiber strength is 100 MPa. Compared with Example 1, this example adopts differential stretching and heating treatment, which proves that this condition significantly improves the fiber strength.
[0076] Example 9
[0077] Weigh 1.5 g of protein-like raw material solid into a glass bottle, add DMSO to a total mass of 10 g, seal and shake at room temperature to dissolve, and obtain a protein-like solution with a mass concentration of 15%. The protein-like solution is centrifuged to remove bubbles and set aside.
[0078] Take 50 mL of methanol and place it in a small plastic cup as a coagulation bath.
[0079] 1 mL of protein-like solution was drawn with a syringe, and the pumping speed was set to 10 μL / min. After the protein-like solution was extruded from the spinneret, the spinneret was placed in a coagulation bath, and the protein-like fibers were formed and precipitated into fibers in the coagulation bath. After stabilization, the fiber heads were taken out and collected on a roller collector at a speed of 1 m / min. The roller collector was set with a rear roller collector at a speed of 5 m / min, and differential stretching was performed to obtain 5-fold stretched protein-like fibers.
[0080] The protein-like fibers were placed in an oven at 120°C for heat treatment for 1 hour.
[0081] The test results of fiber mechanical properties are as follows Fig. 9 As shown, the fiber strength is 200 MPa. Compared with Example 8, this embodiment adopts a higher differential stretching ratio (5 times), which is significantly better than the fiber strength of the corresponding Example 8.
[0082] Example 10
[0083] Weigh 1.5 g of protein-like raw material solid into a glass bottle, add DMSO to a total mass of 10 g, seal and shake at room temperature to dissolve, and obtain a protein-like solution with a mass concentration of 15%. The protein-like solution is centrifuged to remove bubbles and set aside.
[0084] Take 50 mL of methanol and place it in a small plastic cup as a coagulation bath.
[0085] 1 mL of protein-like solution was drawn with a syringe, and the pumping speed was set to 10 μL / min. After the protein-like solution was extruded from the spinneret, the spinneret was placed in a coagulation bath, and the protein-like fibers were formed and precipitated into fibers in the coagulation bath. After stabilization, the fiber heads were taken out and collected on a roller collector at a speed of 1 m / min. The roller collector was set with a rear roller collector at a speed of 8 m / min, and differential stretching was performed to obtain 8-fold stretched protein-like fibers.
[0086] The protein-like fibers were placed in an oven at 120°C for heat treatment for 1 hour.
[0087] The test results of fiber mechanical properties are as follows Fig.10 As shown, the fiber strength is 250 MPa. Compared with Example 9, this embodiment adopts a higher differential stretching ratio (8 times), which is significantly better than the fiber strength of the corresponding Example 9.
[0088] Embodiment 11
[0089] Weigh 1.5 g of protein-like raw material solid into a glass bottle, add DMSO to a total mass of 10 g, seal and shake at room temperature to dissolve, and obtain a protein-like solution with a mass concentration of 15%. The protein-like solution is centrifuged to remove bubbles and set aside.
[0090] Take 50 mL of ethanol and place it in a small plastic cup as a coagulation bath.
[0091] 1 mL of protein solution was drawn with a syringe, and the pumping speed was set to 10 μL / min. After the protein solution was extruded from the spinneret, the spinneret was placed in a coagulation bath, and the protein fiber was formed and precipitated into a fiber in the coagulation bath. After stabilization, the fiber head was taken out and collected on a roller collector at a speed of 1 m / min. The roller collector was set with a rear roller collector at a speed of 10 m / min, and differential stretching was performed to obtain 10-fold stretched protein fiber.
[0092] The protein-like fibers were placed in an oven at 120°C for heat treatment for 1 hour.
[0093] The test results of fiber mechanical properties are as follows Fig.11 As shown, the fiber strength is 300 MPa. Compared with Example 10, this embodiment adopts a higher differential stretching ratio (10 times), which is significantly better than the fiber strength of the corresponding Example 10.
[0094] Example 12
[0095] Weigh 1.5 g of protein-like raw material solid into a glass bottle, add DMSO to a total mass of 10 g, seal and shake at room temperature to dissolve, and obtain a protein-like solution with a mass concentration of 15%. The protein-like solution is centrifuged to remove bubbles and set aside.
[0096] Take 50 mL of isopropanol and place it in a small plastic cup as a coagulation bath.
[0097] 1 mL of protein solution was drawn with a syringe, and the pumping speed was set to 10 μL / min. After the protein solution was extruded from the spinneret, the spinneret was placed in a coagulation bath, and the protein fiber was formed and precipitated into a fiber in the coagulation bath. After stabilization, the fiber head was taken out and collected on a roller collector at a speed of 1 m / min. The roller collector was set with a rear roller collector at a speed of 10 m / min, and differential stretching was performed to obtain 10-fold stretched protein fiber.
[0098] The protein-like fibers were placed in an oven at 120°C for heat treatment for 1 hour.
[0099] The test results of fiber mechanical properties are as follows Fig.12As shown, the fiber strength is 400 MPa. Compared with Example 11, this embodiment uses an isopropanol coagulation bath instead of an ethanol coagulation bath, which proves that the isopropanol coagulation bath is better than the ethanol coagulation bath and is more conducive to improving the mechanical properties of the fiber.
[0100] Example 13
[0101] Weigh 2.5 g of protein-like solid raw material into a glass bottle, add DMSO to a total mass of 10 g, seal and shake at room temperature to dissolve, and obtain a 25% mass concentration protein-like solution. The protein-like solution is centrifuged to remove bubbles for later use. The protein-like fiber is prepared using the electrospinning technology used in the literature (Liao et al., Science 366, 1376-1379).
[0102] Use a syringe to draw 1 mL of the protein-like solution and set the pumping speed to 0.8 mL / h. After the protein-like solution is found to be extruded from the spinneret, turn on the high-voltage power supply for spinning. After the fiber is stable, take out the fiber head and collect it on the roller collector. The roller collector speed is 0.6 m / min.
[0103] The test results of fiber mechanical properties are as follows Fig.13 As shown, the fiber strength is 40 MPa and the ductility is about 150%, which is significantly weaker than the strength of wet-spun protein fibers.
[0104] Embodiment 14
[0105] The mechanical properties of the fibers obtained by dry spinning are taken from the literature (Adv. Mater. 2019, 1904311), and the test results are as follows Fig.14 As shown, the fiber strength is 100 MPa and the ductility is about 750%.
[0106] In summary, Examples 13 and 14 respectively used electrospinning and dry spinning as comparative examples. In addition, the inventors also used melt spinning for experiments, which proved that the strength of fibers prepared by these processes was weaker than that of the protein-like fibers prepared by the method of the present invention.
[0107] The above is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for continuously manufacturing high-strength and high-tenacity protein fibers, characterized in that: The following steps are involved: S1, pumping a protein-like solution with a mass concentration of 15-25% to a spinneret through a catheter, and immersing the spinneret in a coagulation bath solution to form protein-like fibrils in the coagulation bath; S2, using a multi-stage roller collector to continuously draw and collect protein fibrils at a differential speed, with a differential drawing ratio of 2-10 times; S3, putting the collected protein-like fibrils into an oven, and heating them at 90°C-190°C for 10min-120min to obtain a high-strength and high-tenacity protein-like fiber.
2. The method according to claim 1, characterized in that In step S1, the solvent of the protein-like solution is DMSO, DMF, DMA or a mixture thereof in any ratio, and the mass concentration of the protein-like solution is 15-20%.
3. The method according to claim 1, characterized in that In step S1, the coagulation bath solution is water, methanol, ethanol or isopropanol.
4. The method according to claim 1, characterized in that: In step S2, the extrusion speed of the protein solution from a single spinneret is 3 μL / min-50 μL / min.
5. The method according to claim 1, characterized in that In step S2, the differential stretching ratio is 8-10 times.
6. The method according to claim 1, characterized in that In step S3, the heating temperature is 100°C-190°C, and the heating time is 60min-120min.
7. The method according to claim 1, characterized in that The following steps are involved: A protein-like solution with a mass concentration of 15% was pumped to a spinneret through a catheter, and the spinneret was immersed in an isopropanol coagulation bath solution to form protein-like fibrils in the coagulation bath. The extrusion speed of the protein-like solution from a single spinneret was 10 μL / min. The protein fibrils were collected by continuous differential stretching using a multi-stage roller collector, with a differential stretching multiple of 10 times; The collected protein-like fibrils are placed in an oven and heated at 120°C for 60 minutes to obtain a high-strength and high-tenacity protein-like fiber.
8. The method according to claim 1, characterized in that The following steps are involved: A protein-like solution with a mass concentration of 15% was pumped to a spinneret through a catheter, and the spinneret was immersed in an ethanol coagulation bath solution to form protein-like fibrils in the coagulation bath. The extrusion speed of the protein-like solution from a single spinneret was 10 μL / min. The protein fibrils were collected by continuous differential stretching using a multi-stage roller collector, with a differential stretching multiple of 10 times; The collected protein-like fibrils are placed in an oven and heated at 120°C for 60 minutes to obtain a high-strength and high-tenacity protein-like fiber.
9. A high-strength and high-tenacity protein fiber continuously manufactured by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for improving strength and strain of polyurethane fibers
CN110230117A
Preparation method of high-strength and high-toughness bionic fiber
CN114703561A
Preparation method of high-strength and high-toughness artificial spider silk based on double-crosslinking network
CN115305601A
Fiber-based bionic structure polyurethane artificial blood vessel and preparation method thereof
CN116920174A
Spinning process suitable for protein fiber forming
CN117758385A